Early Helicobacter pylori colonisation: the association with growth faltering in The Gambia. Issue 12 (19th November 2004) - Thomas, J E; Dale, A; Bunn, J E G; Harding, M; Coward, W A; Cole, T J; Weaver, L T
Abstract : Background: Helicobacter pylori is one of the commonest causes of chronic infection of mankind, yet the natural history of acute infection is poorly understood. Some studies suggest that gastric colonisation with H pylori is associated with suboptimal nutrition and growth in childhood. Aims: To describe the clinical features of early H pylori colonisation and assess its role in the development of infant malnutrition and growth faltering. Methods: Two consecutive prospective longitudinal cohort studies were conducted at the Medical Research Council Laboratories in a rural community in The Gambia, West Africa. The first birth cohort of 125 infants was followed by a second of 65 children from the same community. H pylori colonisation was detected by sequential 13 C urea breath tests, and infant growth was monitored by serial measurements. Results: Children with early H pylori colonisation became significantly lighter, shorter, and thinner than their peers in late infancy. The association was found in both cohorts. No socioeconomic or demographic confounding variables were identified to explain this, and the weight deficit was no longer detectable when the children were aged 5–8 years. Conclusions: Results suggest that H pylori colonisation in early infancy predisposes to the development of malnutrition and growth faltering, although the effect did not persist into later childhood.